2018
DOI: 10.1016/j.jml.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The nature and consequences of false memories for visual stimuli

Abstract: This paper has been supported by a fellowship from China Scholarship Council (CSC) to Jianqin Wang [No. 201406100057].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 58 publications
(101 reference statements)
4
28
0
Order By: Relevance
“…To rule out this possibility, in Experiment 2, we used the same DRM lists for the word condition and the picture condition, which required a between-subjects design. That is, the word lists were matched with the picture lists such that each picture list was the pictorial form of a word list (see Wang et al, 2018). Another limitation of Experiment 1 was that each reference condition had only four lists, so four critical lures in total, which might reduce the power.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To rule out this possibility, in Experiment 2, we used the same DRM lists for the word condition and the picture condition, which required a between-subjects design. That is, the word lists were matched with the picture lists such that each picture list was the pictorial form of a word list (see Wang et al, 2018). Another limitation of Experiment 1 was that each reference condition had only four lists, so four critical lures in total, which might reduce the power.…”
Section: Discussionmentioning
confidence: 99%
“…The lists were taken from previous studies (Howe, Garner, & Patel, 2013; Wang et al, 2017). The picture lists were pictorial versions of DRM word lists that were normed for image and name agreement (i.e., to what extent the picture represents the DRM concept—see Snodgrass & Vanderwart, 1980; Wang et al, 2018). The picture lists have a mean image agreement rating of 4.22 ( SD = 0.48) on a scale of 1–5 (see Wang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in Koutstaal et al's (2003) study, older adults, who typically have higher false memory rates than younger adults, only made more errors when novel shapes were given verbal labels. Similarly, Wang et al (2018) concluded that false memories from pictures are due to the contributions of conceptual information. Using abstract images as stimuli, Sikora-Wachowicz et al (2019) observed false memories in younger and older adults in a short-term memory task.…”
Section: Manipulations Of Structural Similarity: Phonological and Orthographic Listsmentioning
confidence: 99%